Modifikasi Starter Electric Pada Pompa Alkon Dan Motorized Valve Pada Mu Meter Bandar Udara I Gusti Ngurah Rai Bali.pdf - Haryadi Wibowo, Imam; Samudera Novarizki, Muhammad; Gilang Hafid Bima Nugraha, Kevin; Junaidi, Rahmad; Arista Pradani, Gading; Athaya Daffi Zaidan, Darell; Rivaldo Mea, Yohanes (Jurnal Teknik Mekanikal Bandar Udara, 2024)
odification of the manual or pull starter on the alkon pump to an electric starter using a dynamo starter aims to increase time efficiency related to measuring runway roughness. One time runway roughness measurement is given a time allocation of 1 hour by ATC. For every 1 measurement, there is a test standard, namely a minimum of 8 tests around the runway. In existing conditions, filling water into the tank can only be used for 1 test and the on/off button on the pump must be pressed manually which takes more time because the operator has to get in and out of the car so the operating duration is long. Therefore, to optimize runway roughness testing activities to make them more effective, it is necessary to modify the manual starter on the alcon pump to an electric starter, install an ignition switch on the MU-Meter towing vehicle and install a motorized val